The Equilibrium Real Funds Rate: Past, Present, and Future. Issue Volume 64:Issues 4(2016) (November 2016) - Hamilton, James; Harris, Ethan; Hatzius, Jan; West, Kenneth
Abstract We examine the behavior, determinants, and implications of the equilibrium level of the real federal funds rate, interpreted as the long run or steady state value of the real funds rate. We draw three main conclusions. First, the uncertainty around the equilibrium rate is large, and its relationship with trend GDP growth much more tenuous than widely believed. Our narrative and econometric analysis using cross-country data and going back to the 19th century supports a wide range of plausible estimates for the current level of the equilibrium rate, from a little over 0 per cent to the pre-crisis consensus of 2 per cent. Second, a bivariate vector error correction model that looks only to U.S. and world real rates well captures the behavior of U.S. real rates. The model treats real rates as cointegrated unit root processes. As of the end of our sample (2014), the model forecasts the real rate in the U.S. will asymptote to an equilibrium value of a little less than half a percent by 2021. Consistent with our first point, however, confidence intervals around this point estimate are huge. Third, the uncertainty around the equilibrium rate argues for more "inertial" monetary policy than implied by standard versions of the Taylor rule. Our simulations using the Fed staff's FRB/US model show that explicit recognition of this uncertainty results in a later but steeper normalization path for the funds rate compared with the median "dot" in the FOMC's Summary of Economic Projections.